THE IMPROVEMENT OF COMPANY PERFORMANCE THROUGH RISK MANAGEMENT PROCESS, PERSONNEL CAPABILITY AND THE APPLICATION OF TQM (CASE STUDY: LUBRICANT MANUFACTURING COMPANY PT X) - Yusep Saeful Rizal; Agustinus Hariadi DP (Dinasti International Journal of Education Management And Social Science, 2022)
Performance management is one of the process to achieve a company's vision and mission. The good achievement of company performance is an indicator of the achievement of the company's strategic goals. This research was conducted at a lubricant manufacturing company. The issues faced by the company were a declining market share of sales related to the risk of highly competitive market competition, high levels of losses and rework, and failing to achieve production costs target related to process control methods and resource management. This study aims to determine the effect of risk management processes, personnel capabilities and the application of total quality management (TQM) on company performance. The questionnaire data analysis involved 74 respondents. The data then processed through validity, reliability, classical assumption testing, regression analysis and the coefficient of determination using SPSS. The results of the study showed that the risk management process did not significantly affect the company's performance, the influence of personnel capabilities and the implementation of TQM were positive and significant to the company's performance. The risk management process, personnel capability and TQM implementation simultaneously affect the company's performance positively and significantly.